1986
DOI: 10.1021/bi00353a035
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hydroxyapatite-crystal growth by bone-specific and other calcium-binding proteins

Abstract: Mineralization of bone matrix may be influenced by the presence of specific, noncollagenous bone proteins. The quantitative influence of two bone-specific proteins--bone gamma-carboxyglutamic acid (Gla) protein and osteonectin--and other proteins that decreased the rate of crystal growth was measured by adding seed crystals of hydroxyapatite to a solution of CaCl2 and KH2PO4, pH 7.4 at 37 degrees C. The molar concentrations of proteins needed to inhibit the rate of crystal growth by 50% were as follows: osteon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
172
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(181 citation statements)
references
References 38 publications
8
172
1
Order By: Relevance
“…Damsky and colleagues have demonstrated that osteoblast/fibronectin interactions supply a necessary regulatory signal essential for osteogenic gene expression, with fibronectin possibly playing a role in the recruitment of osteoblast precursor cells (Globus et al, 1995;Moursi et al, 1996;Globus et al, 1998). Finally, osteonectin/SPARC is one of the most abundant noncollagenous proteins found in bone, and it binds strongly to hydroxyapatite (Romberg et al, 1985;Romberg et al, 1986) and collagen I (Kelm, Jr. et al, 1991). Null mutations in osteonectin result in a reduced number of osteoblasts and poor bone maturation, as well as a reduction in matrix production and assembly (Boskey et al, 2003;Delany et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Damsky and colleagues have demonstrated that osteoblast/fibronectin interactions supply a necessary regulatory signal essential for osteogenic gene expression, with fibronectin possibly playing a role in the recruitment of osteoblast precursor cells (Globus et al, 1995;Moursi et al, 1996;Globus et al, 1998). Finally, osteonectin/SPARC is one of the most abundant noncollagenous proteins found in bone, and it binds strongly to hydroxyapatite (Romberg et al, 1985;Romberg et al, 1986) and collagen I (Kelm, Jr. et al, 1991). Null mutations in osteonectin result in a reduced number of osteoblasts and poor bone maturation, as well as a reduction in matrix production and assembly (Boskey et al, 2003;Delany et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Additional work has indicated that osteonectin, and to a lesser extent osteocalcin, could inhibit hydroxyapatite crystal formation. 54 This role seems to prevent excessive mineralization in bone. Osteonectin and osteocalcin are detectable in normal plasma and serum 40,55 and together with osteopontin are also present in human platelets.…”
Section: Role Of Bone-related Noncollagenous Proteins In Atherosclermentioning
confidence: 99%
“…The postulated roles of matrix proteins are diverse: a nucleator by providing certain stereochemical arrangement of charged groups, which is sufficient to lower the activation energy barrier for nucleation of a crystal phase (Glimcher, 1989;Gorski, 1992); or an inhibitor by blocking the growth sites through specific adsorption (Moreno et al, 1979;Termine et al, 1980;Romberg et al, 1986) or by providing spacial constraints as exemplified by the lateral growth of apatitic mineral in calcified turkey tendon (Heywood et al, 1990). Casein phosphoproteins in milk, as cited above, act as a stabilizer of amorphous calcium phosphate in nanometer-sized clusters (Holt et al, 1996).…”
Section: Interaction Between Macromolecules and Calcium Phosphatesmentioning
confidence: 99%